2018
DOI: 10.1111/jrh.12292
|View full text |Cite
|
Sign up to set email alerts
|

National Public Health Data Systems in the United States: Applications to Child Agricultural Injury Surveillance

Abstract: Although these public health data systems captured many details regarding medical aspects of the injury, they included little information on circumstances leading to injury, thus limiting their utility for child agricultural injury surveillance and primary prevention initiatives. We recommend any child agricultural injury data collection tool formally incorporate a structured narrative so underlying circumstances leading to injury events are documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Previous research has argued that work safety interventions have traditionally achieved poor results in influencing safer work environments [5,6,7,8], however, on this point, the authors found contradictory evidence. On the one hand, all farmers seemed to be aware of the most common threats in their environment, and almost all of them made at least some changes to their work safety environment (crediting the intervention that took place one year previously).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous research has argued that work safety interventions have traditionally achieved poor results in influencing safer work environments [5,6,7,8], however, on this point, the authors found contradictory evidence. On the one hand, all farmers seemed to be aware of the most common threats in their environment, and almost all of them made at least some changes to their work safety environment (crediting the intervention that took place one year previously).…”
Section: Discussionmentioning
confidence: 96%
“…The threats farmers perceive encompassed a wider spectrum than previous research has addressed [5,7,8,23,33,45,59]. Just by looking at the most serious/likely perceived threats (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the documented risks, capturing injury and fatality data is increasingly difficult. Several federal and state-funded occupational injury surveillance programs have been eliminated in recent decades, and at present, there is no central database for current US AFF injuries and fatalities [11]. Regional and state-based injury surveillance efforts have had difficulty scaling to the national level, primarily because of the cost to build and sustain a rigorous program.…”
Section: Introductionmentioning
confidence: 99%
“…The epidemiology of pediatric farm injuries is not well‐studied due to limited data sources available and lack of sufficient information regarding injury occurrence . Many studies regarding pediatric farm injuries have involved single‐center‐ or state‐ or regionally specific data, and thus they may not be generalizable.…”
mentioning
confidence: 99%